Understanding the risk of underwater skimming of slow sand filters - Elemo, Tolulope Nwabiani (Cranfield University, 2024)
Abstract This research presents an in-depth examination of underwater skimming (UWS) for cleaning slow sand filters (SSF), as an alternative to the traditional dry skimming (DS). The study explores the risks and advantages of UWS compared to DS methods, particularly in terms of filtration performance, microbial removal effectiveness, and operational efficiencies. The research includes an evaluation of the current state of SSF technology, including operational practices and associated risks faced by operators within the potable water sector, setting the background for identifying the potential improvements that UWS may offer. The study further analyses the risks of particle penetration, head loss development and water quality in SSFs when employing UWS, supported by data from pilot-scale experiments conducted to compare UWS and DS. These experiments compare the effects of UWS against the conventional methods, focusing on filtrate quality, recovery after skimming, and system resilience. Additionally, the study investigates the effects of UWS on dissolved oxygen consumption within the SSF, using a mass balance model to predict the dynamic changes in oxygen levels that occur due to operational disturbances caused by UWS. This aspect of the research highlights the environmental implications of adopting UWS in water treatment practices. One of the key findings from this research is that UWS filters exhibited less disruption post-skimming, allowing for quicker recovery to microbial compliance compared to DS filters. They also maintained more stable microbial water quality immediately post-skim, as evidenced by consistent removals of coliform at 1.9±0.2 log, compared to DS where removals dropped to 1.1±0.4 log. While surface agitation in a worst-case scenario UWS system may increase the likelihood of particle penetration and breakthrough, deeper media depth (>500mm) mitigates this, with particle breakthrough reducing from 2229 no/mL at 200 mm to 53 no/mL at 500mm. Maintaining a 'sweetening flow' during UWS could considerably improve DO supply, and reduce the emergence of anoxic conditions, while considerably reducing the recovery time caused by any flow reductions or pauses. For example, recovery can increase from 10.1-10.9 bed volumes when flow is completely paused, to less than one bed volume with a continuous sweetening flow during skimming. The study maintains that UWS not only addresses the operational challenges posed by traditional methods but also enhances the efficacy and sustainability of SSFs. Through this comprehensive analysis, the research provides substantial evidence that UWS could be instrumental in advancing SSF operation, solidifying its importance as a vital aspect of future research and application in the field. This research contributes to knowledge by demonstrating that UWS enhances the efficacy and sustainability of slow sand filtration systems, reducing operational downtime and maintaining microbial water quality. The potential impact of this research is significant, as it offers a method to increase production capacity from existing SSF assets, potentially transforming slow sand filtration practices globally.
Jefferson, Bruce - Associate Supervisor
Keywords: Slow sand filter (SSF); underwater skimming (UWS); dissolved oxygen (DO); microbial removal; water treatment; water quality; operational efficiency